Hereditary breast cancer: beyond BRCA genetic analysis; PALB2 emerges - Poumpouridou,N.; Kroupis, C. (Clin.Chem.Lab Med., 2012)
Abstract Despite the initial enthusiasm following the discovery of the association of BRCA germline mutations with hereditary breast and/or ovarian cancer, in many families affected by the syndrome no pathogenic mutations were detected in the two genes, although exhaustively searched. Many other genes have also been implicated due to their role in the same pathway of DNA repair where the BRCA1/2 genes are involved: homologous recombination (HR). Among them, PALB2 clearly emerges as the third breast cancer susceptibility gene. Its mutations have been detected in most populations investigated so far, albeit rarely: in 1%-4% of families negative for BRCA mutations, with either partial or complete penetrance. In some populations, PALB2 recurrent mutations have been identified and the estimated hazard risks are comparable to those of BRCA mutations. Since new effective targeted therapeutic options are becoming available ("synthetic lethality" with novel PARP inhibitors, etc.) that are applicable to all those patients with a defect in HR pathway, it is imperative to detect all these candidate patients. Data obtained from laboratory tests in the tumor (simple immunohistochemistry, gene expression analysis, etc.) can assist in the recognition of a specific pattern (BRCA1ness, HRless) so that even patients that look "sporadic" could benefit from these targeted therapies. Therefore, a genetic analysis algorithm is proposed, although with the advent of Next Generation Sequencing it is predicted that in the future most germline genetic alterations and also somatic or epigenetic events in the tumor of these genes will be detected
Keywords: analysis; Breast Neoplasms; Diagnosis; DNA repair; Fanconi Anemia; genetics; Greece; Homologous Recombination; Humans; Nuclear Proteins; therapy; Tumor Suppressor Proteins